(11)C-MK-8278 PET as a tool for pharmacodynamic brain occupancy of histamine 3 receptor inverse agonists - Van Laere, Koenraad J; Sanabria-Bohórquez, Sandra M; Mozley, David P; Burns, Donald H; Hamill, Terence G; Van Hecken, Anne; De Lepeleire, Inge; Koole, Michel; Bormans, Guy; de Hoon, Jan; Depré, Marleen; Cerchio, Kristine; et al. (The Journal of nuclear medicine (1978), 2014)
The histamine 3 (H3) receptor is a presynaptic autoreceptor in the central nervous system that regulates the synthesis and release of histamine and modulates the release of other major neurotransmitters. H3 receptor inverse agonists (IAs) may be efficacious in the treatment of various central nervous system disorders, including excessive daytime sleepiness, attention deficit hyperactivity disorder, Alzheimer disease, ethanol addiction, and obesity. Using PET and a novel high-affinity and selective radioligand (11)C-MK-8278, we studied the tracer biodistribution, quantification, and brain H3 receptor occupancy (RO) of MK-0249 and MK-3134, 2 potential IA drugs targeting cerebral H3 receptors, in 6 healthy male subjects (age, 19-40 y). The relationship among H3 IA dose, time on target, and peripheral pharmacokinetics was further investigated in 15 healthy male volunteers (age, 18-40 y) with up to 3 PET scans and 3 subjects per dose level. The mean effective dose for (11)C-MK-8278 was 5.4 ± 1.1 μSv/MBq. Human brain kinetics showed rapid high uptake and fast washout. Binding potential values can be assessed using the pons as a reference region, with a test-retest repeatability of 7%. Drug RO data showed low interindividual variability per dose (mean RO SD, 2.1%), and a targeted 90% RO can be reached for both IAs at clinically feasible doses. (11)C-MK-8278 is a useful novel PET radioligand for determination of human cerebral H3 receptor binding and allows highly reproducible in vivo brain occupancy of H3-targeting drugs, hereby enabling the evaluation of novel compounds in early development to select doses and schedules.